From French Polynesia to France: The Legacy of fa'a'amu Traditional Adoption in "International" Adoption - Leblic, Isabelle (Anthropologica, 2014)
In French Polynesia, as in New Caledonia, circulation of children is frequent and just as accepted as the movement of women inside kinship systems. Fa'a'amu adoption involves open, direct adoption arrangements between extended family members, and this has gradually included international ones. Since 1970, many fa'a'amu babies have also been given to French childless couples. The adaptation of the fa'a'amu institution allows us to trace the legacies of this practice in a globalized world. The Kanak adoption tradition provides comparative material that illuminates the new relationships and parenthood(s) found in the "West," thereby contributing to current debates in kinship.